2016
DOI: 10.1038/srep27965
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic hepatocyte dedifferentiation is accompanied by upregulation of mesenchymal markers, protein sialylation and core alpha 1,6 linked fucosylation

Abstract: Alterations in N-linked glycosylation have long been associated with cancer but for the most part, the reasons why have remained poorly understood. Here we show that increased core fucosylation is associated with de-differentiation of primary hepatocytes and with the appearance of markers indicative of a transition of cells from an epithelial to a mesenchymal state. This increase in core fucosylation was associated with increased levels of two enzymes involved in α-1,6 linked fucosylation, GDP-mannose 4, 6-deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 70 publications
(108 reference statements)
2
24
0
Order By: Relevance
“…Core fucosylation is elevated in liver and ovarian cancerous tissues in comparison to normal (Abbott et al, 2008; Mehta et al, 2016), and linked with EGFR dimerization and activation, TGF-β-activation, and HGF and EGF signaling pathways (Gu et al, 2013; Liu et al, 2011; Wang et al, 2015). However, a role for this enzyme in melanoma and the specific core fucosylated glycoproteins underlying its effects are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Core fucosylation is elevated in liver and ovarian cancerous tissues in comparison to normal (Abbott et al, 2008; Mehta et al, 2016), and linked with EGFR dimerization and activation, TGF-β-activation, and HGF and EGF signaling pathways (Gu et al, 2013; Liu et al, 2011; Wang et al, 2015). However, a role for this enzyme in melanoma and the specific core fucosylated glycoproteins underlying its effects are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that these fucosylated antigens facilitate the invasion and spread of tumor cells [72][73][74][75]. In relation to cancer, a study conducted in 2016 by Mehta et al [76] showed that the increase in central fucosylation is associated with the dedifferentiation of primary hepatocytes and with the appearance of markers that are indicative of the transition of the cells from an epithelial to a mesenchymal state [76]. Another study reported that the inhibition of the fucosylation of annexin A4 inhibited cell proliferation in ovarian clear cell carcinoma [77].…”
Section: Discussionmentioning
confidence: 99%
“…In our recent study, we showed that increased core fucosylation was directly associated with de-differentiation of hepatocytes and the transition of cells from an epithelial to a mesenchymal state (EMT)(48). However, this modification was not present in the all patients and may be directly related to the underlying genetic abnormalities associated with the cancer.…”
Section: Discussionmentioning
confidence: 99%